Study of Polyelectrolyte Adsorbent Theory on a Repulsive Charged Surface (Journal of Atomic and Molecular Sciences, 2014)
Applying scaling theory of polyelectrolyte adsorption, and according to ratioof the dielectric constant between the medium and the substrate, and taking intoaccount strong interaction between polyelectrolytes of multivalency adsorption, weproposed a scaling theory of the approximation method on a repulsive charged surface.It is divided into two kind phase diagrams that one is qualitatively different.This shows when the surface charge density is low (or the bulk counterion densityis high), the surface and the bulk counterion density are almost the same. Once thesurface charge density is high enough, counterions condense on the surface. In thisregime, polyelectrolytes of lower valency form a correlated many-chain state. As theirvalency is high enough, the state turns out to be single-chain because of stronger repulsionbetween neighboring chains.
Keywords: dielectric constant; polyelectrolyte; charged of surface; adsorbent theory.